2023
DOI: 10.1111/mpp.13315
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear effectors of plant pathogens: Distinct strategies to be one step ahead

Abstract: Nuclear effector proteins released by bacteria, oomycete, nematode, and fungi burden the global environment and crop yield. Microbial effectors are key weapons in the evolutionary arms race between plants and pathogens, vital in determining the success of pathogenic colonization. Secreted effectors undermine a multitude of host cellular processes depending on their target destination. Effectors are classified by their localization as either extracellular (apoplastic) or intracellular. Intracellular effectors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…For example, Wang et al [ 54 ] identified the key susceptible gene TaPsIPK1 in the host plant through the pathogenic effector protein PsSpg1 of wheat stripe rust fungus, opening up a new avenue for molecular breeding of disease-resistant wheat using modern gene editing techniques. The CYP450 enzymes play crucial roles in virulence, adaptation to host environments, evasion of host immune responses, and mycotoxin formation in many plant pathogens [ 55 ], such as V. dahliae [ 56 ], Nectria haematococca [ 57 ], and F. graminearum [ 58 ]. Further analysis of F. zanthoxyli effectors revealed that 50 sequences also had CAZymes characteristics and most of them belong to the class of GHs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al [ 54 ] identified the key susceptible gene TaPsIPK1 in the host plant through the pathogenic effector protein PsSpg1 of wheat stripe rust fungus, opening up a new avenue for molecular breeding of disease-resistant wheat using modern gene editing techniques. The CYP450 enzymes play crucial roles in virulence, adaptation to host environments, evasion of host immune responses, and mycotoxin formation in many plant pathogens [ 55 ], such as V. dahliae [ 56 ], Nectria haematococca [ 57 ], and F. graminearum [ 58 ]. Further analysis of F. zanthoxyli effectors revealed that 50 sequences also had CAZymes characteristics and most of them belong to the class of GHs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence microscopy analysis indeed confirmed the nuclear subcellular localization of all protein fusions studied, but more detailed research will be required to verify the involvement of the in silico-predicted NLS in the import of the effectors into the plant nucleus, because some of the fusion proteins were also detected within other subcellular compartments, such as the cytosol. It might be interesting to test whether the NLS of the investigated effectors is the sole responsible for the effector's translocation into the nucleus via the canonical a/b-importin pathway or whether, in contrary, effectors can passively diffuse through the nuclear pores, as they display molecular weights below 40 kDa (Liu and Coaker, 2008;Harris et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial effectors have a wide range of possible final locations in planta ranging from the apoplastic space to different intracellular compartments including the nucleus. This allows effectors to find their specific targets and control multiple cellular processes 1719 . Nuclear effectors have been shown to modulate hormonal pathways, host metabolism or immune responses by different mechanisms that include interactions with nuclear proteins, DNA or RNA 17,19 .…”
Section: Introductionmentioning
confidence: 99%
“…This allows effectors to find their specific targets and control multiple cellular processes 1719 . Nuclear effectors have been shown to modulate hormonal pathways, host metabolism or immune responses by different mechanisms that include interactions with nuclear proteins, DNA or RNA 17,19 . Interestingly from the five effectors characterized in the fungus Rhizophagus irregularis , three are located in the nucleus 12,14,16 This might reflect the large number of predicted nuclear effectors in this fungus, as revealed in an analysis of R. irregularis secretome during symbiosis, in which from ca.…”
Section: Introductionmentioning
confidence: 99%